Irradiation after surgically induced brain injury in the rat: timing in relation to severity of radiation damage - (:unkn) unknown (KLUWER ACADEMIC PUBL, 2004)
The aim of this study was to evaluate how timing of irradiation after brain surgery in rats relates to overall extent of brain radiation damage. Extent of injury was determined according to lipid peroxidation ( malondialdehyde; MDA) levels in brain tissue. Thirty female rats were randomly assigned to five equal groups ( Groups A - E). Four groups underwent trephination and scalpel hemisection of right frontal lobe. Rats in Groups B and D received 25 Gy cranial irradiation in a LINAC system at 10 and 20 days after surgery, respectively. Twenty-four hours later they were killed and their right frontal lobes were removed for lipid peroxidation determination. Groups A and C were not irradiated; these groups were killed and had their frontal lobes removed on day 11 and day 21 post-surgery, respectively. The remaining six animals ( Group E, sham surgery) underwent trephination only, and were killed and had their frontal lobes removed 24 h later. There was a significant difference between the mean MDA levels in the control group and Group D, and between the levels in Group B and Group D ( P < 0.05 for both). The difference between the mean for Group A and the mean for Group B was even more significant ( P < 0.01). The most striking differences were between the control group and Group B, and between Group B and Group C ( P < 0.001 for both). The data from this rat model suggest that, in humans, starting radiotherapy early ( 1 - 2 weeks) after debulking of a brain tumor may result in significantly higher levels of tissue damage than if the radiation is started 3 weeks or more postoperatively. Further experimental research is needed to project these findings in rats to human subjects.
Keywords: brain; free radicals; injury; lipid peroxidation; radiation; surgery; VITAMIN-E; HEMOSIDERIN; RADIOSURGERY; GENERATION; REDUCTION; MELATONIN